2022
DOI: 10.31949/agrivet.v10i1.2727
|View full text |Cite
|
Sign up to set email alerts
|

ANALISIS EFISIENSI PEMASARAN BAWANG MERAH (Allium ascalonicum L.) DI KELURAHAN MALUMBI KECAMATAN KAMBERA KABUPATEN SUMBA TIMUR

Abstract: Adanya rantai pemasaran bawang merah yang panjang dan selisih harga ditingkat pelaku pemasaran menyebabkan para petani mendapatkan pendapatan yang tidak sesuai dengan apa yang mereka inginkan. Tujuan penelitian ini adalah untuk mengetahui pola saluran pemasaran, margin pemasaran dan efisiensi pemasaran usahatani bawang merah di Kelurahan Malumbi, Kecamatan Kambera,Kabupaten Sumba Timur. Sampel diambil sebanyak 45 petani dengan teknik simple random sampling. Untuk sampel pada saluran pemasaran dengan menggunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Of the three channels, marketing channel 1 for shallots in East Lombok Regency is more efficient than marketing channel 2 and marketing channel 3. The results of this study are the same as those of Saragih et al, (2022 ) who found that the three marketing channels for shallots were classified as efficient.…”
Section: Shallots Marketing Efficiencysupporting
confidence: 83%
See 1 more Smart Citation
“…Of the three channels, marketing channel 1 for shallots in East Lombok Regency is more efficient than marketing channel 2 and marketing channel 3. The results of this study are the same as those of Saragih et al, (2022 ) who found that the three marketing channels for shallots were classified as efficient.…”
Section: Shallots Marketing Efficiencysupporting
confidence: 83%
“…These marketing actors form 3 shallot marketing channels where channel 1 includes farmers, villagelevel collectors, retailers, and consumers, channel 2 namely farmers, village-level collectors, districtlevel collectors, retailers, consumers, and channel 3, namely farmers, village-level collectors, wholesalers -retailers -consumers. The number of marketing channels for shallots in this study is the same as the number of marketing channels in the research by Olabu et al, (2022) and Saragih et al, (2022) where there are 3 marketing channels for shallots. However, it is different from the research (Ali et al, 2015) where there are 2 marketing channels for shallots, and the research by Marbun et al, (2018) where there are 4 marketing channels for shallots.…”
Section: Shallot Marketing Channelmentioning
confidence: 99%
“…Improving efficiency is one of the common goals of farmers, marketing institutions, and consumers. High efficiency reflects good marketing performance while low efficiency means the opposite (Saragih et al, 2022a).…”
Section: Marketing Efficiencymentioning
confidence: 99%
“…It can be concluded that the longer marketing agency has been in business, the more it will comprehend the market share become an expert in the market is response to. The consistency possessed by a marketing agency will become a separate consideration for the consumers, thus it is providing high loyalty to the agency (RAHAYU et al, 2019;Saragih et al, 2022b).…”
Section: Characteristics Of Marketing Institution Respondentsmentioning
confidence: 99%